Viajando pela educação da primeiríssima infância: sentidos, crenças e valores que sustentam os saberes e as práticas pedagógicas na/da creche - Rodrigues, Silvia Adriana [UNESP] (2016)
This paper was developed linked to the line of research "Childhood and Education", and aims to present the results of research that had as study object the educational nursery environment - understood as a learning space (adults and children) to share and product a new knowledge and to live in the early childhood. According with the basic assumptions that in collective educational spaces, into the adult-child interactions, the role of the more experienced partner (in this case the teacher) is guided by the views and perceptions of the cultural group to which it belongs, which, in turn, direct the look on the child, its particular ways to understand and give meaning to its surroundings (physical and social), I defined as the central theme of this discussion the understanding that the meanings, values and beliefs that drive the pedagogical actions/practices of professionals who working in this space need to be “unveiled”. So I had delimited as the main objectives of this research to learn how the nursery institution has been performed its role to be a space for the promotion of human development, seeking to understand how professionals understand their own social role and the nursery’s role, adopting the principle that these both are configured as a privileged way of view, not as the entire nursery phenomenon, according its breadth, but one of the nodal points of its dynamic operation, based on the personal perception that it’s a responsibility of the professionals to “set the tone” or “stay the course” in the daily work of collective education institutions. There are also specific objectives: to understand how early childhood professionals realize the nursery environment, how they see and value this space and its social function; searching the ways of understanding the professional nursery (at training and at different times of action) on training, the knowledge and necessary actions for educational practice with little children; to discuss about interference (positive and negative) of understandings and beliefs (and hence actions) of professionals in the process of human development and children’s learning. Therefore, the research, inserted within the qualitative field of educational research, with exploratory character, had five subjects participants with different profiles, with the procedure for data collection using what I have called ‘the practice reports’, a hybrid instrument which brings elements of the interview and narrative in its constitution. The data analysis, performed using as its basic method the discourse analysis of Bakhtin’s ideology and his active responsive reading proposal, allowed me to ratify the understanding that the nursery is presented as polysemic and polyphonic space; there are multiple representations, perceptions, ideas, beliefs, values, thoughts, speeches and consequently practices, which make up what has materialized as an educational institution of the early childhood that, largely, lacks ruptures and changes in different aspects such as interpersonal relationships (between adults and children) more qualified; daily pedagogical organization grounded in play interactions and children's interests; effective articulation between the inseparable practices of care and educate, the value of training in specific courses, but also the daily built knowledge, among others. It was also possible to understand that teaching in this level of education (but not only in it) is built in a tangle of mixed possibilities that occurs along its trajectory (personal and professional), occurring in many ways. There are many remnants of interpretations ruled in ancient conceptions (but also very recent) about the child, childhood, kindergarten and teacher's role that must be overcome, giving way to an education understanding for younger children in collective spaces with social functions and specific educational, and, mainly, as a children right to be respected and promoted more effectively, a challenge presented to the training courses, but also for all segments involved in the causes of the early childhood education.